2020
DOI: 10.11113/umran2020.6n3-2.423
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Konsep IKHLAS Dalam Menyantuni Anak Istimewa (Autisme) (Implementation of IKHLAS Concept In Treating Special Needs)

Abstract: The World Health Organization (WHO) in 2017 revealed one in 160 children having an autism in this world and its prevalence is increasing globally. These statistics clearly show many parents out there struggling with the great challenge of raising and educating these special children. They also face greater stress than parents with normal children and children with other disabilities such as down syndrome. The objective of this study was to examine alternative mechanisms to help parents cope with the reality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…According to Bujang et al (2020), knowledge of the meaning of ASD is important so that there is no neglect when dealing with ASD children. This lack of knowledge can lead to negative attitudes towards ASD children and their families.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Bujang et al (2020), knowledge of the meaning of ASD is important so that there is no neglect when dealing with ASD children. This lack of knowledge can lead to negative attitudes towards ASD children and their families.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the literature has also provided coping strategies for parents and practitioners in dealing with children with autism. Bujang et al (2020) advocated the IKHLAS concept which is one such way to provide parents and practitioners with a way to help cope with children with ASD. The IKHLAS concept is comprised of the following words: Ilmu (knowledge), Kasih sayang (loving), Harapan (hope), Latihan dan intervensi (training and intervention), Amanah (Trust), and Sokongan (Support).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is shown that ability to communicate and socialise are important to therapy practitioners. Next, Bujang et al (2020) stated that knowledge is one of the ways to handle children with ASD in his concept IKHLAS. In addition, social interaction, communicative skills, and behavioural difficulties are the most focused programmes in rehabilitation centres (Ceccarelli et al, 2020).…”
Section: Skills Needed By Therapy Practitionersmentioning
confidence: 99%
See 2 more Smart Citations